Marilogiasociale. Il significatodella Vergine per lasocietà - Gregorius Pasi (Studia Philosophica et Theologica, 2021)
On the one hand, Mary is an integral part of living the Catholic faith. On the other hand, social action is an integral part of the mission of the Church. The correlation between the two is less articulated in mariological reflection. Clodovis M. Boff in his book “Marilogia sociale. Il significato della Vergine per la società” proposes “social mariology” as a theological reflection that brings together the figure of Mary and the social mission of the Church. The distinctive contribution of this book is in the formulation of the problematics, epistemological principles and references to the loci theologici of social mariology.